CRISPR/Cas9-Mediated Targeted Mutagenesis of CYP93E2 Modulates the Triterpene Saponin Biosynthesis in Medicago truncatula - Confalonieri, Massimo; Carelli, Maria; Gianoglio, Silvia; Moglia, Andrea; Biazzi, Elisa; Tava, Aldo (Frontiers in Plant Science, 2021)
In the Medicago genus, triterpene saponins are a group of bioactive compounds extensively studied for their different biological and pharmaceutical properties. In this work, the CRISPR/Cas9-based approach with two single-site guide RNAs was used in Medicago truncatula to knock-out the CYP93E2 and CYP72A61 genes, which are responsible for the biosynthesis of soyasapogenol B, the most abundant soyasapogenol in Medicago spp. No transgenic plants carrying mutations in the target CYP72A61 gene were recovered while fifty-two putative CYP93E2 mutant plant lines were obtained following Agrobacterium tumefaciens-mediated transformation.Among these, the fifty-one sequenced plant lines give anediting efficiency of 84%. Sequencing revealed that these lines had various mutation patterns at the target sites. Four T0 mutant plant lines were further selected and examined for their sapogenin content and plant growth performance under greenhouse conditions. The results showed that all tested CYP93E2 knock-out mutants did not produce soyasapogenols in the leaves, stems and roots, and diverted the metabolic flux towards the production of valuable hemolytic sapogenins. No adverse influence was observed on the plant morphological features of CYP93E2 mutants under greenhouse conditions. In addition, differential expression of saponin pathway genes was observed in CYP93E2 mutants in comparison to the control. Our results provide new and interesting insights into the application of CRISPR/Cas9 for metabolic engineering of high-value compounds of plant origin and will be useful to investigate the physiological functions of saponins in planta.